Feederism Eating, Weight Gain, and Sexual Pleasure - Charles, Kathy. (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
This book explores the controversial and misunderstood world of sexualised weight gain known as feederism. Conversations with over 20 feeders and feedees are analysed through a psychological and sociological lens. The implications for health professionals working in bariatrics are discussed along with directions for future research.